To what Extent Can the Diversity of Qur’anic Tafsir be Described as ‘Traditions of Reason’ - Dhulkifli, Muhammad Luthfi (UIN Sunan Kalijaga Yogyakarta, 2023)
This paper examines tafsir as one of the oldest scientific disciplines developed by Muslims, who experienced dialectical shifts from time to time. Early tafsir was characterized by the bi al-mathur tradition or by its reliance on riwayah sources. While it is commonly argued that this mode of interpretation leaves no place for the mufassir's intervention, his subjectivity and rationality in choosing the preferred tradition cannot be ignored. Following that, tafsir evolved according to the bi al-ra'yi tradition which is believed to emphasize the mufassir’s reasoning while interpreting the Qur’an. This paper is addressed to examine this categorization, using Sherman Jackson’s traditions of reason that aim to compromise tafsir with varying hues of traditionalist and rationalist perspectives. This paper employs the library method by reviewing relevant literature to answers the main question. In the end, the limitations of a tafsir can be accepted as traditions of reason as long as the interpretation adheres to the fundamental criteria of interpretation. This includes mufassir’s profound understanding, no conflict with other verses or hadith, and, in many cases, its conformity with logic. Traditional and Rational elements are complementary and must be addressed proportionately. The emphasis on reason has the potential to lead to the mufassir's personal preferences and biases. Meanwhile, the usage of traditional riwayah will limit interpretive space and the context's applicability.